Urgent need for updating the slogan of global climate actions from "tree planting" to "restore native vegetation". Issue 3 (26th November 2021) - Tölgyesi, Csaba; Buisson, Elise; Helm, Aveliina; Temperton, Vicky M.; Török, Péter
Abstract : The prevailing nature‐based solution to tackle climate change is tree planting. However, there is growing evidence that it has serious contraindications in many regions. The main shortcoming of global tree planting is its awareness disparity to alternative ecosystem types, mainly grasslands. Grasslands, where they constitute the natural vegetation, may support higher biodiversity and a safer, soil‐locked carbon stock than plantations and other forests. We suggest replacing "tree planting" by "restore native vegetation." This improved action terminology reduces the risks of inappropriate afforestation and, by diversifying target ecosystem types, does not reduce but increases potential land area for nature‐based climate mitigation.